2001
DOI: 10.1212/wnl.57.4.671
|View full text |Cite
|
Sign up to set email alerts
|

Increased glutamate in CSF and plasma of patients with HIV dementia

Abstract: Increased CSF glutamate may originate within the CNS and may play a pathogenetic role in HIV dementia, thus supporting the treatment of these patients with glutamate receptor antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 26 publications
2
102
0
Order By: Relevance
“…18,19 In this context, HIV-1 Vpr mediates many processes that facilitate HIV-1 infection and promote persistence in the host cells. 3,13 Our earlier studies using SILAC-based proteomics analysis demonstrated that numerous enzymes in the glycolytic pathway and TCA cycle were altered in response to HIV-1 Vpr in macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 In this context, HIV-1 Vpr mediates many processes that facilitate HIV-1 infection and promote persistence in the host cells. 3,13 Our earlier studies using SILAC-based proteomics analysis demonstrated that numerous enzymes in the glycolytic pathway and TCA cycle were altered in response to HIV-1 Vpr in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…16 HAD has been linked to macrophage toxin production including glutamate. [17][18][19][20] Increased glutamate levels are also seen in the plasma, and cerebrospinal fluid (CSF) of HIV-1 infected patients. 18,21 In addition, the observation that soluble Vpr is detected in the CSF of HIV-1 infected individuals 22 suggests that Vpr can have bystander effects on uninfected cells and on neuronal cells 23 and contribute to glutamate-mediated neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Since high levels of glutamate inhibit the proliferation of T-cells, glutamate has been related to immune deficiency (Ferrarese et al, 2001). Most attention has been focused on mGluR expression in thymocytes and T lymphocytes.…”
Section: Immune System and Thymusmentioning
confidence: 99%
“…Increased Glu has been found in CSF of acute MS patients (154) and secondary progressive MS (155). Excess glutamate has also been found in HAD patient populations (156). Increases in extracellular glutamate are known to occur through a variety of mechanisms including reversal of glutamate uptake carriers, impairment of membrane integrity, swellinginduced opening of anion channels, compromise of the blood brain barrier and enzymatic conversion of glutamine to glutamate (157).…”
Section: Excess Generation Of Extracellular Glutamate In Hadmentioning
confidence: 99%